2019
DOI: 10.1016/j.foreco.2018.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of wild ungulates on the structure, composition and succession of temperate forests

Abstract: This version is distributed under a non-commercial no derivatives Creative Commons (CC-BY-NC-ND) user license, which permits use, distribution, and reproduction in any medium, provided the original work is properly cited and not used for commercial purposes. Further, the restriction applies that if you remix, transform, or build upon the material, you may not distribute the modified material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 53 publications
1
49
0
1
Order By: Relevance
“…Large herbivores steer temperate forest composition in two major ways: Preferential browsing and grazing of more palatable species such as broadleaved tree species, and intense physical disturbance such as trampling or uprooting, which can eliminate entire cohorts of seedlings and samplings from forest stands [44]. Our study confirmed the protective function of the thorny shrubs.…”
Section: Discussionsupporting
confidence: 75%
“…Large herbivores steer temperate forest composition in two major ways: Preferential browsing and grazing of more palatable species such as broadleaved tree species, and intense physical disturbance such as trampling or uprooting, which can eliminate entire cohorts of seedlings and samplings from forest stands [44]. Our study confirmed the protective function of the thorny shrubs.…”
Section: Discussionsupporting
confidence: 75%
“…Although our study was only conducted in Michigan, northern hardwood forests cover millions of hectares from Minnesota to the Canadian Maritimes. Furthermore, many temperate mesic forests worldwide are similarly characterized by high ungulate populations and reduced tree recruitment [60,61]. Even larger extents of forest may be affected by insects and pathogens, that are often introduced and that create widespread overstory mortality and a dense regeneration layer with little chance of overstory recruitment.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Exlosures of these Guam ungulates have revealed restoration can be rapid [38,39], and soil chemical traits are among the important ecological processes that are restored following ungulate exclosure [40,41]. Physical disturbance of the litter and soil is one means by which non-native ungulates damage ecosystem processes such as nutrient cycling [42][43][44][45][46]. Moreover, the Integrated Natural Resources Management Plan (INRMP) that was guiding all DoN activities at this time was published in 2012 [47], and stated that an ecosystem approach would guide management to "restore and maintain ecological processes" that included "nutrient cycles."…”
Section: Case 5 Multiple Approved Practitioners Accessing the Same Cmentioning
confidence: 99%